A modified JH2 model with improved strength model, damage evolution, and equation of state for rock under impact and blasting loads. (November 2022) - Shu, Yun; Zhu, Zheming; Wang, Meng; Wang, Fei; Ren, Li; Li, Yaojia
Abstract: Rock fragmentation by blasting is widely applied in geotechnical engineering, requiring the development of the rock damage constitutive model. A modified Johnson-Holmquist Ceramic (M-JH2) model, which adds an initial yield strength surface, is proposed to characterize the rock damage process under blasting loads. In addition, a new damage scale factor was proposed to capture the strain hardening and gradual softening behaviors. Tensile and compressive damages are treated separately to describe the tensile-compressive asymmetry, and the volumetric plastic strain is introduced into the compressive damage. Moreover, the EOS of the original JH2 model is modified by including unloading and reloading paths. To calibrate the model, benchmark examples were established in the LS-DYNA with the M-JH2 models, such as single element tests, Split Hopkinson Pressure Bar test, rock blasting fracture, and crater blasting field test. The results show that the M-JH2 model agrees well with the classic experiments. The M-JH2 model improves the JH2 model in strain hardening, gradual softening, and the sensitivity difference of damage evolution between tension and compression in a Brazilian disc dynamic splitting test. Highlights: A modified JH2 (M-JH2) model is proposed to better characterize the rock damage process under impact and blast loads. An initial yield surface, a new damage scale factor, and the tensile-compressive asymmetry are added. The new model is improved in hardening, softening, and the sensitivity difference between tension and compression damages.